KEPUTUSAN MEMBELI KONSUMEN DI WARUNG MAKAN KAKI LIMA DI SURABAYA-INDONESIA - Indrawati, Mei; Sama, I Wayan (JWM (JURNAL WAWASAN MANAJEMEN), 2024)
The tight competition between food stalls scattered in the corners of the city, on the roadside in Surabaya, requires marketers to know the factors that influence someone to buy food at street food stalls. Researchers use the factors of service quality, product, and price as determining factors for someone to make a purchase at a street food stall. The population in this study were all food buyers at street food stalls. Determination of a sample of 120 people was carried out purposively with quota sampling. The research was conducted from March 2023 to April 2023. The results of the research on service quality, products, and prices affect purchasing decisions at street food stalls.